Cutaneous Adverse Drug Reactions: Regional Experience of a Global Challenge - Bushehri, Behzad; Mokhtarpoor, Akbar; Bahrami, Ehsan; Ghorani-Azam, Adel (Current Drug Safety, 2024)
Background: Adverse drug reactions (ADR) are considered any harmful and unintended side effects associated with the use of a drug at the usual therapeutic dose, in which skin is involved in most cases. Therefore, the availability of epidemiological information on reactions, reaction patterns, and their causative drugs can be helpful in timely diagnosis and necessary measures, such as caution in prescribing causative drugs to prevent these types of reactions. Methods: In this retrospective descriptive study, the archived files of patients with dermatoses due to ADR referred to Taleghani University Hospital, Urmia, Iran, during 2015-2020 were studied. Patterns and frequency of skin reactions, demographic data, and the frequency of chronic comorbidities were identified. Results: A total of 50 patients with drug-induced skin rash were found, of which 14 were male (28%) and 36 were female (72%). Skin rashes were most frequently found in patients aged 31-40 years. In 76% of patients, there was at least one chronic underlying disease. The most common reaction pattern was maculopapular rash (44%), and the most common causative drugs were antiepileptic drugs (34%) and antibiotics (22%). Mortality was found in 4 cases, which was due to antibiotics and antiepileptic drugs that caused toxic SJS/TEN and erythroderma. The hospital stays were highest in SJS and lowest in a maculopapular rash. Conclusion: Knowledge about the epidemiology and the frequency of adverse drug reactions may be helpful in increasing the awareness of physicians for correct and rational drug prescriptions, which can reduce unnecessary hospital referrals and treatment costs.
Keywords: side effects